Hybrid ion exchange resins for phosphorus removal from wastewater. - Muhammad, Ahsan (Cranfield University, 2017)
Phosphorus is not only a non-renewable resource but also a major cause of eutrophication in natural environments. Accordingly, legislation aims to control point source discharges from wastewater treatment with new targets likely to be as low as 0.1 mg Lˉ¹. Current wastewater treatment options for phosphorus removal, based on either biological or chemical processes, are capable of meeting the new consents. However, challenges exist with both such that alternative approaches are required. One of the most promising is the use of hybrid ion exchange resins where ferric oxide nanoparticles have been embedded within the structure of the base resin. The aim of the current thesis is to understand and critically evaluate the technical and economic challenges associated with using the hybrid resin for phosphorus removal. Technical assessment demonstrates the efficacy of the resin in meeting the new standard as either a polishing process or as the main treatment unit for phosphorus removal. Elucidation of the impact of background water constituents revealed the importance of the ferric oxide nanoparticles in conjunction with targeted regeneration to enable effective removal in complex matrices. Batch experiments revealed that a combination of pseudo-second order and intra particle diffusion models can be used to model the system. The media capacity was maximum (8.5 mg gmediaˉ¹) in the first cycle and reduced to a more consistent 2.5 – 3.7 mg gmedia-1 between cycle 3 to 9. Adsorption of nitrate ions from the wastewater effluent was found to cause the most inhibition to the removal of phosphorus, followed by sulphate and then humic acid. Column trials establish the effectiveness of the process even at very low contact times of 0.5 to 1 minute. However, optimum operation was achieved around empty bed contact times of 3-5 minutes as these generate extended serviceable bed life. The media can remove phosphorus down to 0.1 mg P Lˉ¹ for treating both, full phosphorus load (at sites with no other phosphorus removal mechanism) and for phosphorus polishing (at sites where phosphorus concentration has been to reduced to ~1 mg Lˉ¹ through existing treatment). Furthermore, the resin also removed COD at a level between 40-50%, making it suitable for sites needing organic polishing. Economic analysis revealed the process offered a plausible economic alternative to standard solutions to meet low phosphorus consents. For small works (2,000 PE), HAIX fixed bed system was found to be economically competitive below empty bed contact time of 7 minutes. For medium works (20,000 PE), this increased to an empty bed contact time of 10 minutes. A mobile clean-up system for the regenerant (NaOH) has been deemed more economical for small works (2,000 PE), whereas the chemical quantity needed for medium works (20,000 PE) required an on-site clean-up system. The potential to substantially reduce total costs were identified such that confidence can be placed in the economic suitability of the solution. Importantly, the economic plausibility of the process did not require inclusion of the sale of the recovered phosphate product such that the technology is appropriate within both linear and circular economic models.
Keywords: Phosphorus; hybrid ion exchange resin; circular economy